Gender Analysis of Women's Empowerment by Village Government (Study in Rea Village, Binuang District, Polewali Mandar) - Tenrilawa, Dian Furqani; Nuraliah, Dewi; Pratiwi, Andi Dewi; Syarif, Ahmad Arif (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to analyze women's empowerment in the village government from the gender aspect. The type of research is field research located in Rea Village, Binuang District, Polewali Regency. Data were collected through interviews, document studies and literature. The collected data were analyzed with a qualitative analysis model. The results of this study reveal that, women's empowerment in the Rea Village Office, Binuang District, Polewali Regency has been seen. This is evidenced by the process of recruiting village officials who are balanced between men and women and human resource development programs specifically for women. However, some gender analysis instruments have not been fulfilled, such as the fulfillment of the WID (Women in Development) and GAD (Gender and Development) policy matrices. This is due to the absence of resources (village officials) that focus on gender analysis in empowering women in village institutions.